Conotrachelus dimidiatus Champion, 1904 (Coleoptera: Curculionidae: Molytinae): morphological re-description of the immature stages, keys, tribal comparisons and biology - Torres, Betzabeth Cecilia Pérez; Skuhrovec, Jiří; Marín-Cevada, Vianey; Elizalde-González, María P. (Zootaxa, 2018)
The mature larva and pupa of Conotrachelus dimidiatus Champion, 1904 (Curculionidae: Molytinae) are morphologically re-described, keyed and, for the first time, compared with known larvae and pupae of other Conotrachelus species. The chaetotaxy of the larval and pupal body in the genus Conotrachelus is probably strictly uniform. The immature stages of described species are also compared with available data on the immature stages of genera from several tribes in the subfamily Molytinae. All larvae of Conotrachelus have a distinct endocranial line of a different size and a frons with only three setae. The states of these two distinct characteristics in larvae of the eight known Conotrachelus species are constant and unique compared to other tribes in the subfamily Molytinae. In Central Mexico, overwintering Conotrachelus beetles emerge in July and then feed and mate on host plants. Larvae are endophagous within the fruits. In September and October, the larvae pupate in the soil. This new information will be very useful in the application of pesticides to the fight against this well-known pest in Mexico.